2003
DOI: 10.1021/jp027301a
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Hydroxyl Radical with Acetone. 1. Kinetics of the Reactions of OH, OD, and18OH with Acetone and Acetone-d6

Abstract: The rate coefficient for the reaction of OH with acetone, k 1 , was measured by producing OH via pulsed laser photolysis and detecting it via laser-induced fluorescence to be k 1 (T) ) 1.38 × 10 -13 + 3.86 × 10 -11 exp(-1997/T) cm 3 molecule -1 s -1 . These results confirm the rate coefficient data of Wollenhaupt et al. (J. Phys. Chem. A 2000, 104, 2695. A value of k 1 suitable for atmospheric calculations is deduced from our data and that from previous work to be k 1 ) 1.39 × 10 -13 + 3.72 × 10 -11 exp(-2044… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 22 publications
8
74
0
1
Order By: Relevance
“…Following the rate constants for the reactions of OH with acetone as a function of temperature is out of scope since they were previously studied, and the corresponding activation parameters were reported 5. Studies focusing on the gas‐phase reactions suggested that (R‐1) may proceed by two mechanisms, through an H‐abstraction mechanism or by addition via intermediate H‐bonded complexes 20–25. The recent kinetic and product studies for the reactions of OH with acetone in the aqueous phase 18 identified reaction products that correspond (i) to the oxidation of the weakest CH bond into a carbonyl function and (ii) to the oxidation of the weakest CH bond into a hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Following the rate constants for the reactions of OH with acetone as a function of temperature is out of scope since they were previously studied, and the corresponding activation parameters were reported 5. Studies focusing on the gas‐phase reactions suggested that (R‐1) may proceed by two mechanisms, through an H‐abstraction mechanism or by addition via intermediate H‐bonded complexes 20–25. The recent kinetic and product studies for the reactions of OH with acetone in the aqueous phase 18 identified reaction products that correspond (i) to the oxidation of the weakest CH bond into a carbonyl function and (ii) to the oxidation of the weakest CH bond into a hydroxyl group.…”
Section: Resultsmentioning
confidence: 99%
“…Our new measurements and previous rate measurements for k H and k D are 4 Wollenhaupt et al, 5 and Vasvári et al 6 are more consistent with our measurements, all lying ϳ12%-13% higher, and that of Tranter and Walker 8 at 753 K, derived from the influence of acetone on H 2 /O 2 chemistry, is 20% higher. Gierczak et al 9 recently published kinetic measurements of OH, OD, and 18 OH with acetone and acetoned 6 . Their results also indicate 14% and 31% higher rate constants at 298 K compared to our results for acetone and acetone-d 6 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…1, [2][3][4][5][6][7][8][9] and it may be seen that while different experiments have yielded different activation energies, overall there is good agreement between the magnitude of the k values. There is an unusual temperature dependence, with k increasing with T above room temperature, and decreasing much more slowly, or perhaps even increasing slightly, at lower temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…A beam splitter allowed the simultaneous recording (on a reference photodiode) of incident light intensity, I 0 . Literature values (in 10 −19 cm 2 molecule −1 ) of σ X =6.65 and 11.8 (Dillon et al, 2005), 22.0 (Salahub and Sandorfy, 1971), and 30.1 (Gierczak et al, 2003) were used to determine concentrations for respectively X=CH 3 OH, C 2 H 5 OH, (CH 3 ) 2 CHOH and CH 3 C(O)CH 3 via the Beer-Lambert relationship, Eq. (1).…”
Section: Reagent Handling and Concentration Measurementsmentioning
confidence: 99%